Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/diagnostics12112594
|View full text |Cite
|
Sign up to set email alerts
|

PSMA PET-CT in the Diagnosis and Staging of Prostate Cancer

Abstract: Prostate cancer is the most common cancer and the second leading cause of cancer death in men. The imaging assessment and treatment of prostate cancer has vastly improved over the past decade. The introduction of PSMA PET-CT has improved the detection of loco-regional and metastatic disease. PSMA PET-CT also has a role in the primary diagnosis and staging, in detecting biochemical recurrence after curative treatment and in metastasis-directed therapy. In this paper we review the role of PSMA PET-CT in prostate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 127 publications
(142 reference statements)
0
19
0
4
Order By: Relevance
“…In a recent meta-analysis, PSMA PET-CT showed sensitivity and specificity in a pooled analysis of 0.97 and 0.66, respectively, with a negative likelihood ratio of 0.05 for the primary diagnosis of prostate cancer in patients with clinical suspicion, with use of the pathologic report as the reference. Furthermore, a retrospective analysis reported that PSMA PET-CT showed higher sensitivity for clinically significant prostate cancer compared with multiparametric magnetic resonance imaging (mpMRI) (94.85% vs. 86.03%; p=0.022) [ 4 5 ].…”
Section: Usefulness Of Psma As a Primary Diagnostic Modality For Pros...mentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent meta-analysis, PSMA PET-CT showed sensitivity and specificity in a pooled analysis of 0.97 and 0.66, respectively, with a negative likelihood ratio of 0.05 for the primary diagnosis of prostate cancer in patients with clinical suspicion, with use of the pathologic report as the reference. Furthermore, a retrospective analysis reported that PSMA PET-CT showed higher sensitivity for clinically significant prostate cancer compared with multiparametric magnetic resonance imaging (mpMRI) (94.85% vs. 86.03%; p=0.022) [ 4 5 ].…”
Section: Usefulness Of Psma As a Primary Diagnostic Modality For Pros...mentioning
confidence: 99%
“…The authors concluded that PSMA PET might replace traditional imaging for staging high-risk prostate cancer. The Appropriate Use Criteria for PSMA PET also commented that PSMA PET could be indicated for primary staging of unfavorable intermediate- and high/very high-risk prostate cancer, especially if CT and bone scintigraphy show distant metastasis of five or fewer lesions [ 4 5 6 ]. Despite these previous studies suggesting substantially improved diagnostic values of PSMA PET for primary prostate cancer, PSMA PET has not yet achieved the level needed for a strong recommendation in the current guidelines.…”
Section: Usefulness Of Psma As a Primary Diagnostic Modality For Pros...mentioning
confidence: 99%
See 1 more Smart Citation
“…The introduction of PSMA-PET has revolutionised the diagnostics of metastatic disease, increasing the detection of metastases and allowing for an earlier discovery of location and quantity of metastatic spread [41]. This allows for a more accurate classification and possibly earlier commencement of treatment, potentially increasing the likelihood of treatment success [42].…”
Section: Optimising Patient Selectionmentioning
confidence: 99%
“…The advent of prostate-specific radiotracers (notably prostate-specific membrane antigen [PSMA]) allows the detection of previously occult micrometastatic disease. 4 For localized PCa not requiring WPRT or to boost the primary disease, brachytherapy-the temporary or permanent placement of sealed radioactive sources ("seeds")-is an appropriate treatment option. Accurate permanent seed placement in low dose rate (LDR) brachytherapy requires ultrasound guidance, while temporary seed placement in high dose rate (HDR) brachytherapy can be accomplished with ultrasound or computed tomography (CT) guidance.…”
mentioning
confidence: 99%